1992
DOI: 10.1159/000468796
|View full text |Cite
|
Sign up to set email alerts
|

More on Effects of Storage Time and Temperature on Urinary Enzymes: A 1-Year Study

Abstract: Results of our conclusive study on urinary enzyme stability during sample storage are reported. We measured alanine aminopeptidase (AAP) and N-acetyl-β-D-glucosaminidase (NAG) in morning urines from 9 healthy normal subjects immediately after collection and throughout a 1-year storage at -70 and -20 °C. AAP proved to be quite stable at -70 °C (99.2% of the basal value at the end of the year). NAG is partially preserved (84.1 % of the basal value) at -70 °C, but significantly decreased (50.4%) at -20 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Previous validation studies using human urine have shown NAG activity to be stable at À70 1C for a period of 1 year. 24 Urine NAG activity (U/L) was standardized to urine creatinine concentration to give the NAG index. Urine samples were excluded from analysis of proteinuria, albuminuria, and NAG index, if there was evidence of a urinary tract infection, bacteriuria, pyuria, or gross hematuria.…”
Section: Protocol For Collection and Storage Of Blood And Urine Samplesmentioning
confidence: 99%
“…Previous validation studies using human urine have shown NAG activity to be stable at À70 1C for a period of 1 year. 24 Urine NAG activity (U/L) was standardized to urine creatinine concentration to give the NAG index. Urine samples were excluded from analysis of proteinuria, albuminuria, and NAG index, if there was evidence of a urinary tract infection, bacteriuria, pyuria, or gross hematuria.…”
Section: Protocol For Collection and Storage Of Blood And Urine Samplesmentioning
confidence: 99%
“…Analysis of covariance (ANCOVA) models also controlled for age [17,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], gender [16,17,20,22,[36][37][38][39][40][41][42][43][44][45][46], race [35][36][37][45][46][47][48][49], lean body mass, and storage time [50][51][52][53][54][55][56][57][58][59][60][61], as effects of these factors ...…”
Section: Discussionmentioning
confidence: 99%
“…In practice, storage at or below 4°C will slow down the degradation of sample constituents. However, loss of enzyme activity after low-temperature storage (Matteucci et al, 1991) would indicate that there are perceptible changes to the macromolecules. By and large, the effects of storage depend on the nature of chemical species and the storage conditions.…”
Section: Sample Storagementioning
confidence: 99%